PERHITUNGAN PRODUKSI OVERBURDEN DENGAN MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) DAN NILAI OEE DARI EXCAVATOR KOBELCO SK-200 - Vitri Rospitasari; Diana Purwandari; Aditya Budi Nugraha (LPPM Universitas Bina Bangsa, 2023)
PT. Starindo Sakti Award is the place to carry out this research which is located in Pangandaran. This study uses the Overall Equipment Effectiveness (OEE) method to optimize mining equipment in achieving production targets for overburden stripping. Overall Equipment Effectiveness (OEE) is a method that has been accepted globally to measure the level of a company and the potential for improvement of the production process. Overall Equipment Effectiveness (OEE) aims to evaluate the performance of an equipment used in industry. The factors to be calculated on the OEE component are: Availability Factor, Utilization Factor, Speed ​​Factor, Bucket Factor, Overall Equipment Effectiveness (OEE) of Equipment. The results of the calculation of overburden production using the OEE method after improving working time by reducing standby time and increasing operating hours, the overburden production obtained from the Kobelco SK-200 excavator is 20,160.22 BCM. While the Overall Equipment Effectiveness (OEE) value of the Kobelco SK-200 excavator after repairs is 60%.